Some thoughts about time - Kleinert, Ulfrid (Socialinė teorija, empirija, politika ir praktika, 2003)
The conceptions of time are presented in the paper. The first conception of time is connected to the ancient Greek word Chronos. The word Chronos denotes the time as a measure of movement. It defines the time section – the meeting date in calendar, expressed in the number of hours, days, weeks, months and years. The second conception of time is expressed in ancient Greek word – Kairos. The word Kairos denotes the events, which signify the change. That is the moment when the things are changed. It is a time of change. The third conception of time is defined as personal time. That is our personal time, when we are with our self. The fourth conception of time is named social time. That is time, when we are with other.